Guidelines for the future operation of selected Caribbean regional information networks as commercial ventures - Evan-Wong, Sue ([CCCRIS] [Georgetown]GY, 1995)
Sets out guidelines for the operation of CARISPLAN, CARPIN, CTCS, ECLAC AMBIONET and OECS.INFONET as commercial ventures. Notes that the current policy constraints will prevent most of the networks from providing their services and products on a profit generating basis, but hopes that adjustments could be made to their information policies.